2011
DOI: 10.1088/1475-7516/2011/09/033
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation coefficients from scalar and fermion quantum field interactions

Abstract: Dissipation coefficients are calculated in the adiabatic, near thermal equilibrium regime for a large class of renormalizable interaction configurations involving a two-stage mechanism, where a background scalar field is coupled to heavy intermediate scalar or fermion fields which in turn are coupled to light scalar or fermion radiation fields. These interactions are typical of warm inflation microscopic model building. Two perturbative regimes are shown where well defined approximations for the spectral funct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
210
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(216 citation statements)
references
References 82 publications
5
210
1
Order By: Relevance
“…while the inflaton is decaying; in the radiation-dominated era the relative contribution will fall again. 9 Note that in the radiation-dominated era, the blocking term again decreases in magnitude, and we expect the resonance to become unblocked a second time as in [8].…”
Section: Efficiency Of Particle Productionmentioning
confidence: 90%
See 1 more Smart Citation
“…while the inflaton is decaying; in the radiation-dominated era the relative contribution will fall again. 9 Note that in the radiation-dominated era, the blocking term again decreases in magnitude, and we expect the resonance to become unblocked a second time as in [8].…”
Section: Efficiency Of Particle Productionmentioning
confidence: 90%
“…The topic of the perturbative dissipation of a scalar in a thermal background has been studied in the context of warm inflation [9]. Related work [10] discusses thermal effects on an oscillating scalar field coupled to a generic fermion, covering the dissipative effect of the thermal bath, modification of the scalar potential, the formation of non-topological solitons and non-perturbative particle production.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we have recently shown that warm inflation can be consistently realized in a simple quantum field theory framework requiring very few fields, the Warm Little Inflaton scenario [19], where the required flatness of the inflaton potential is not spoiled by thermal effects (see also refs. [20][21][22][23][24][25][26] for earlier alternative models), paving the way for developing a complete particle physics description of inflation that can be fully tested with CMB and Large-Scale Structure (LSS) observations and possibly have implications for collider and particle physics data.…”
Section: Jhep02(2018)063mentioning
confidence: 99%
“…We neglect all chemical potentials for simplicity. The corresponding decay widths are given by [23] Γ (B)…”
Section: Jhep02(2018)063mentioning
confidence: 99%
See 1 more Smart Citation